2016
DOI: 10.1186/s12889-016-3345-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing disclosure among women experiencing intimate partner violence during pregnancy in Moshi Municipality, Tanzania

Abstract: BackgroundIntimate Partner Violence (IPV) has serious negative health effects to millions of women around the globe. While disclosing IPV could open doors for support and eventually prevent partner abuse, the factors associated with IPV disclosure during pregnancy are not well known. The aim of this study was to examine factors influencing IPV disclosure to any person of interest or organization supporting women during pregnancy in Moshi Municipality, Tanzania.MethodsData were from a prospective cohort study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 28 publications
3
37
1
Order By: Relevance
“…This finding is supported by a study conducted in Tanzania, which showed that women who are considered inferior by other community members were more likely to feel ashamed to seek help and, as a result, they hide and continue suffering in silence [ 36 ]. Socially isolated women are also less likely to join supportive groups hence decreasing their chances to be supported by other informal and formal support networks [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is supported by a study conducted in Tanzania, which showed that women who are considered inferior by other community members were more likely to feel ashamed to seek help and, as a result, they hide and continue suffering in silence [ 36 ]. Socially isolated women are also less likely to join supportive groups hence decreasing their chances to be supported by other informal and formal support networks [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experiencing physical violence during pregnancy was associated with unwanted birth outcomes of preterm birth and low birth weight [ 13 ]. Victims of physical violence during pregnancy were also more likely to disclose their experience to natal relatives than those with other forms of partner violence [ 22 ]. This sample was therefore selected to understand their experiences with partner violence, their decision-making process for disclosure to natal relatives and support received.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While literature from low- and middle-income countries (LMIC) focuses on violence against women in the general population (Hamberger & Larsen, 2015 ; Katiti et al , 2016 ), pregnancy has been identified as a period of increased risk for exposure to intimate partner violence (IPV) (WHO, 2011 ; Bernstein, et al , 2016 ). IPV is a well-documented phenomenon of behaviour in the context of human relationships (WHO, 2005 ; Sarkar, 2008 ; Silva et al , 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…ARCHES providersare trained to respond in a supportive and validating manner, and to never coerce or pressure a patient in any way to disclose either IPV or RC. This approach acknowledges that many women and girls do not disclose abuse to providers, or feel that is safe or appropriate to seek help from providers for GBV (32)(33)(34).Women who do disclose IPV are offered to be connected by the provider via phone to a trained counselor from a local GBVsurvivor support agency at the close of their clinic visit (i.e. a "warm referral"); this approach has been shown to reduce barriers to referral uptake (trust of service providers, perception that services are not appropriate for their situation) (35,36).…”
Section: Arches Intervention For Implementation In Kenyamentioning
confidence: 99%